PCR Mutation Detection Protocols - Theophilus, Bimal D. M.; Rapley, Ralph (Methods in Molecular Biology, 2002)
Application of DNA technology to the identification of disease-causing mutations has become widespread in recent years. PCR Mutation Detection Protocols, provides biological and clinical investigators with a comprehensive collection of new, recent, and updated PCR-based screening methods suitable for detecting the presence of both known and novel mutations. The methods cover point mutations (e.g., ASO-PCR, SSCP, DGGE, chemical cleavage), deletions (multiplex PCR, FISH, blotting), non-sense mutations (PTT), and more. The new and exciting techniques of DNA array analysis, along with such recently developed experimental methods as conformation-sensitive gel electrophoresis, are also included. Additional coverage is given to the direct use of DNA sequencing as a detection method in its own right and to the characterization of mutations previously located by other screening techniques. Each chapter explains the basic theory behind the technique and provides valuable notes essential for its successful execution. Comprehensive and highly practical, PCR Mutation Detection Protocols assures both seasoned and novice investigators access to the highly productive and readily reproducible PCR-based mutation detection methods, techniques that are laying the groundwork for many of today's major scientific and medical advances